2020
DOI: 10.18378/rvads.v15i4.7958
|View full text |Cite
|
Sign up to set email alerts
|

Eficiência agronômica e qualidade sanitária de biofertilizantes aplicados no solo em cultivo orgânico da alface

Abstract: A adubação de hortaliças por meio de biofertilizantes é utilizada principalmente pela agricultura orgânica. No entanto, são escassos os trabalhos publicados avaliando a microbiota potencialmente patogênica a humanos nos biofertilizantes, assim como sua formulação conforme as necessidades nutricionais da cultura. Desse modo, o objetivo com este estudo foi formular dois biofertilizantes otimizados, avaliar suas características sanitárias (microbiológicas e parasitológicas) e eficiência agronômica no cultivo orgâ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The "Trophobiosis Theory" (Chaboussou, 1987) underlies the management practices used to obtain the nutritional balance of the plants. Experiments based on this theory showed that, in excess, fertilization with N, K, Ca and Mg, as well as pesticides, T he cultivation of tomatoes in organic systems has advantages over the conventional system due to the greater economic return to the farmer (Melo & Silva, 2012;Souza & Garcia, 2013), protection of the environment (Mazzei et al, 2021) and production of fruits with better quality, bringing flavor, health, food and nutritional security to the consumer (Nascimento et al, 2013;Vieira et al, 2014).…”
Section: Received On October 4 2022; Accepted On February 2 2023mentioning
confidence: 99%
“…The "Trophobiosis Theory" (Chaboussou, 1987) underlies the management practices used to obtain the nutritional balance of the plants. Experiments based on this theory showed that, in excess, fertilization with N, K, Ca and Mg, as well as pesticides, T he cultivation of tomatoes in organic systems has advantages over the conventional system due to the greater economic return to the farmer (Melo & Silva, 2012;Souza & Garcia, 2013), protection of the environment (Mazzei et al, 2021) and production of fruits with better quality, bringing flavor, health, food and nutritional security to the consumer (Nascimento et al, 2013;Vieira et al, 2014).…”
Section: Received On October 4 2022; Accepted On February 2 2023mentioning
confidence: 99%
“…Lettuce (Lactuca sativa L.) stands out nationally as an important hydroponic crop (Cometti et al, 2019), due to its high yield, earliness and market acceptance. It is rich in nutrients that are important for human health, being the leafy vegetable most consumed in Brazil (Moura et al, 2020).…”
Section: Introductionmentioning
confidence: 99%